TEKA-TEKI SILANG IBUPERI UNTUK MENINGKATKAN INGATAN SISWA DALAM MEMPELAJARI MATERI KINGDOM ANIMALIA - Wahyuni, Naning (Jurusan Pendidikan Bahasa, Fakultas Ilmu Budaya, Universita Brawijaya, 2022)
Kingdom Animalia is one of the class X material which is declared difficult not only by the students but also by the teacher. The broad scope of the material, the many scientific names and foreign Latin terms make it difficult for students to learn it. Classroom Action Research using Ibuperi's Crossword Puzzle which is applied in the Think Pair Share (TPS) learning model is carried out to overcome the problems experienced by students. The pretest, posttest and questionnaire data about the use of the Ibuperi's Crossword Puzzle obtained were analyzed descriptively and qualitatively. The subjects in this study were students of class X MIPA 3 SMAN Taruna Nala, East Java. The result of this research showed that the use of Ibuperi's Crossword Puzzle which is applied in the TPS learning model can help students remember Latin terms found in Kingdom Animalia material, as evidenced by the gradual increase in posttest results.